Emergence of an optrA-positive Enterococcus faecalis ST699 lineage in animal-derived foods in Beijing, China - Chuncai Liang; Yizhu Chen; Xuan Wu; Rui Chang; Wenkai Cao; Ling Wei; Hui Li; Bing Shao (International Journal of Food Microbiology, 2026)

Multi-scale mechanistic elucidation of hydrogen generation in chemical looping gasification of lignite using carbide slag - Xujie Luo; Senlin Dong; Jie Yang; Binbin He; Dongyang Li; Liping Ma; Bing Huang; Liang Chen; Qihong Cen; Heping Zeng; Rui Nie; Lan Shao (Journal of Environmental Chemical Engineering, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Freeze-thaw damage evolution and crack propagation failure mechanism of red sandstone under non-uniform water distribution conditions - Li Wenbo; Sun Jielong; Chen Rui; Wang Yu; Wen Ziyi; Lou Bing (Transportation Geotechnics, 2026)

Ecotoxicological impacts of TNT and its key transformation intermediates in freshwater microcosms and their effective remediation by a bicarbonate-activated peroxide system - Xu Yang; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo; Yong-bing Zhu; San-ping Zhao (Journal of Water Process Engineering, 2026)

Differential volatile-omics analysis for tamarind (Tamarindus indica L.) and aroma-active compounds identification via DMU-SPME-GC-MS method - Rui-Hua Jin; Ling Zhang; Li-Bo Qi; Chun-Mei Yuan; Zi-Bo Song; Jia-Teng Chen; Ming Du; Xian-Bing Xu (Food Chemistry, 2026)

Quantifying land-use-specific non-point source pollution in a forest-dominated watershed using control-section mass balance and ridge regression - Zhang Jing; Zhao Rui-rui; Yang Lu Ping; Chen Zi Jing; Xing Bing; Peng Shi-tao (Process Safety and Environmental Protection, 2026)

Biocontrol potential of Burkholderia cenocepacia P3 against maize gray leaf spot: induction of defense signaling and rhizosphere microbiome modulation - Peiyuan Wang; Liu Wang; Lu Zheng; Rui Chen; Xin Pu; Bing He (Physiological and Molecular Plant Pathology, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Multifunctional interface engineering enables high efficiency of semi-transparent CsPbBr3 solar cells - Ankang Shu; Mingming Li; Jiawei Song; Zhengyang Li; Qian Wang; Shangwei Huang; Jiahao Cheng; Wenjian Shen; Cong Geng; Rui Chen; Guijie Liang; Jun Yao; et al. (Chemical Engineering Journal, 2026)

Excavation Damage Evaluation of Rock Anchor Beam Based on Acoustic P-Wave Velocity and RFD Index in Highly Stressed Powerhouse: A Case Study of Baihetan Hydropower Station, China - Jin-Shuai Zhao; Lei Xia; Yong Fan; Quan Jiang; Bing-Rui Chen; Guang-Dong Yang; Dong-Ze Wang (Rock Mechanics and Rock Engineering, 2026)

Efficient combined use of electroacupuncture with ordered collagen scaffolds enhances the therapeutic efficacy of human spinal cord-derived neural progenitor cells therapy in spinal cord injury rats - Yunlong Zou; Weiwei Xue; Bo Guo; Lu Li; Yannan Zhao; Xianming Wu; Zhifeng Xiao; Qi Zhang; Dezun Ma; Xinhao Zhao; Bing Chen; He Shen; et al. (Science China Life Sciences, 2026)

Model scale approach to assess the seakeeping performance of a foil-assisted unmanned catamaran - Bing Zheng; Qiaowen Yu; Shigang Wang; Weimin Chen; Zhiyuan Geng; Rui Deng (Ocean Engineering, 2026)

Submicron biochar induces developmental toxicity, oxidative stress, and DNA damage in zebrafish (Danio rerio) - Anying Chen; Bing Wang; Ping Li; Qianwei Feng; Rui Wang (Chemosphere, 2026)

A new risk for the recovered Tibetan antelope (Pantholops hodgsonii): Co-exposure of microplastics with organophosphates in their habitats - Rui Guo; Caian He; Jian Sun; Shaohua Li; Chuntao Zhao; Zhiyong Ling; Liang Chen; Wenrui Zhang; Jingmeng Li; Bing Wang; Jufang Hu; Dongmei Yu; et al. (Journal of Hazardous Materials, 2025)

Impact of thallium contamination on microbial communities and biogeochemical cycles in freshwater ecosystems - Shuang Yan; Yongxin Bing; Qianli Ma; Rui Zhao; Xiaodie Cai; Yuyin Yang; Sili Chen; Shuguang Xie (Aquatic Ecology, 2025)

Research on Environmental Response Characteristic of Super-Long Inclined Shaft Tunnel and CO Diffusion and Ventilation Optimization of Blasting Procedures - Kong-fei Yu; Huai-bing Wang; Hong-yan Wang; Chen-qi Fan; Bu-rui Liu; Xuan-ke Ren (Applied Geophysics, 2025)

Photocatalytic biorefining green closed-loop: Photocatalytic alkali lignin depolymerization in supramolecular solvent - Chengcheng Suo; Xiaochang Zhang; Xinai Li; Jifang Zhang; Hongru Zhang; Rui Teng; Wei Li; Sha Luo; Bing Tian; Qingjiang Pan; Chunhui Ma; Zhijun Chen; et al. (Journal of Environmental Chemical Engineering, 2025)

Spatiotemporal evolution and driver analysis of wastewater greenhouse gas emissions in Chinese mainland: Insights and future trends - Yang Chen; Rui Qiu; Min Zheng; Bing-Jie Ni; Hong-Guang Guo (Environmental Research, 2025)

Stabilizing zinc anode with multifunctional glycine copper additive - Lang Chen; Yue Tian; Bing-Chen Liu; Bo-Xuan Zhang; Kang-Rui Ren; Zhuo-Yun Song; Pengfei Wang; Zonglin Liu; Qianyu Zhang; Jie Shu; Ting-Feng Yi (Chemical Engineering Journal, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Endothelial Cell Integrin α6 Regulates Vascular Remodeling Through the PI3K/Akt-eNOS-VEGFA Axis After Stroke - Bing-Qiao Wang; Yang-Ying Duan; Mao Chen; Yu-Fan Ma; Ru Chen; Cheng Huang; Fei Gao; Rui Xu; Chun-Mei Duan (Neuroscience Bulletin, 2025)

Predicting estrogen receptor agonists from plastic additives across various aquatic-related species using machine learning and AlphaFold2 - Wen-Jun Shi; Zhou Cao; Xiao-Bing Long; Chong-Rui Yao; Jin-Ge Zhang; Chang-Er Chen; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Droplet-vitrification for cassava shoot tip cryopreservation: protocol optimization and histological observation for rapid shoot tip recovery - Min-Rui Wang; Xiu-Qing Miao; Yun-Liu Fu; Lang-Xin Chen; Xiao-Bing Wang; Qing-Quan Yang; Li Xu; Zhiying Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Combined genome and transcriptome provides insight into the genetic evolution of an edible halophyte Suaeda salsa adaptation to high salinity - Bing Cui; Ranran Liu; Qiong Yu; Jianrong Guo; Xihua Du; Zixin Chen; Chenyang Li; Tong Wang; Ru Liu; Rui He; Congcong Song; Yue Liu; et al. (Molecular Ecology, 2025)
Suaeda salsa L. is a typical halophyte with high value as a vegetable. Here, we report a 447.98 Mb, chromosomal‐level genome of S. salsa , assembled into nine pseudomolecules (contig N50 = 1.36 Mb) and annotated with 27,927 annotated protein‐coding genes. Most of the assembled S. salsa genome, 58.03%, consists of transposable elements. Some gene families including HKT1 , NHX , SOS and CASP related to salt resistance were significantly amplified. We also observed expansion of genes encoding protein that bind the trace elements Zn, Fe, Cu and Mn, and genes related to flavonoid and α‐linolenic acid metabolism. Many expanded genes were significantly up‐regulated under salinity, which might have contributed to the acquisition of salt tolerance in S. salsa . Transcriptomic data showed that high salinity markedly up‐regulated salt‐resistance related genes, compared to low salinity. Abundant metabolic pathways of secondary metabolites including flavonoid, unsaturated fatty acids and selenocompound were enriched, which indicates that the species is a nutrient‐rich vegetable. Particularly worth mentioning is that there was no significant difference in the numbers of cis ‐elements in the promoters of salt‐related and randomly selected genes in S. salsa when compared with Arabidopsis thaliana , which may affirm that plant salt tolerance is a quantitative rather than a qualitative trait in terms of promoter evolution. Our findings provide deep insight into the adaptation of halophytes to salinity from a genetic evolution perspective.

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Quantification of water-soluble moroxydine hydrochloride residue using UPLC-MS/MS: Development and validation in 22 different complex plant-based food samples - Rui Zhang; Xuan Zhu; Liqian Chen; Yan He; Min Zhao; Bing Qian; Bingjun Han (Food Chemistry, 2025)

Effects of earthworms on the performance of Lolium multiflorum, soil properties and microbial communities in its root-zone soil under cadmium stress - Xiao-Gai Wang; Bing-Nan Zhao; Zi-Yang Xie; Zhi-Huan Chen; Zhi-Hang Liu; Xiao Chen; Bo-Yang Lu; Jia-Ning Liu; Rui Zhang; Chao Si (Plant and Soil, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Correlation of lipid hydrolysis, oxidation, and molecular transformation with volatile compound revolution in pork during postmortem wet-aging process - Kaihua Zhang; Rui Hao; Shouwei Wang; Zheqi Zhang; Dan Li; Xiaoman Li; Bing Zhao; Shunliang Zhang; Yan Zhao; Xiangning Chen (Food Chemistry, 2025)

Occurrences of heavy metal in breast milk in China: Results of the third national breast milk survey - Rui Wang; Jiangkun Yu; Dawei Chen; Jingguang Li; Kemin Qi; Lan Ma; Bing Lyu; Xiaohong Shang; Yunfeng Zhao (Journal of Hazardous Materials, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Enhanced electron transport through hydrogen bonds and Ag nanoparticles in the PCN-222/Ag/COF core–shell photocatalyst for efficient oxytetracycline degradation - Bing-Bing Lu; Jia-Chang Lu; Qing-Yun Zhao; Rui Wang; Ze-Lin Chen; Ji-Qiang Guan; Hao Liu; Ying Fu; Fei Ye (Journal of Cleaner Production, 2025)

A rapid increase of groundwater in 2021 over the North China Plain from GPS and GRACE observations - Rui Zhang; Yujie Peng; Nengfang Chao; Qi Ou; Gang Chen; Zhengtao Wang; Hong Zhu; Bing Liu; Zixin Zhang (GPS Solutions, 2025)

Calcium alginate-biochar composite immobilized A. ferrooxidans effectively removes sulfate and ferric iron from acid mine drainage - Rui Li; Bing Wang; Bin Gao; Lei Li; Pan Wu; Xueyang Zhang; Miao Chen; Qianwei Feng (Journal of Environmental Management, 2024)

Analysis of deliquescent chloride salt by laser-induced breakdown spectroscopy with controlled uniform precipitation - Lizhu Kang; Ji Chen; Zhijie Huang; Zhanjian Lin; Rui Zhang; Bing Lu; Xiangyou Li (Analytica Chimica Acta, 2024)

A granular thermodynamic constitutive model considering THMC coupling effect for hydrate-bearing sediment - Rui Zhou; Bing Bai; Liang Chen; Yongchen Zong; Nan Wu (Ocean Engineering, 2024)

Application of machine learning in the study of development, behavior, nerve, and genotoxicity of zebrafish - Rui Wang; Bing Wang; Anying Chen (Environmental Pollution, 2024)

Short-term exposure to ambient fine particulate matter constituents and myocardial infarction mortality - Yingxin Li; Bing Lu; Jing Wei; Qingqing Wang; Wancheng Ma; Rui Wang; Ruijun Xu; Zihua Zhong; Lu Luo; Xi Chen; Ziquan Lv; Suli Huang; et al. (Chemosphere, 2024)

Environmental pollution of paraben needs attention: A study of methylparaben and butylparaben co-exposure trigger neurobehavioral toxicity in zebrafish - Jing Xiang; Bing-Rui Lv; Ya-jun Shi; Wen-ming Chen; Ji-liang Zhang (Environmental Pollution, 2024)

Populus euphratica R2R3-MYB transcription factor RAX2 binds ANN1 promoter to increase cadmium enrichment in Arabidopsis - Caixia Yan; Bing Feng; Ziyan Zhao; Ying Zhang; Kexin Yin; Yi Liu; Xiaomeng Zhang; Jian Liu; Jing Li; Rui Zhao; Nan Zhao; Xiaoyang Zhou; et al. (Plant Science, 2024)

In-situ comprehensive investigation of deformation mechanism of the rock mass with weak interlayer zone in the Baihetan hydropower station - Jin-Shuai Zhao; Bing-Rui Chen; Quan Jiang; Ding-Ping Xu; Ben-Guo He; Shu-Qian Duan (Tunnelling and Underground Space Technology, 2024)

Large-scale soil application of hydrochar: Reducing its polycyclic aromatic hydrocarbon content and toxicity by heating - Hongyu Si; Rui Wang; Yuqing Zhao; Han Hao; Changkai Zhao; Sen Xing; Hewei Yu; Xiaohui Liang; JiKai Lu; Xiuxiu Chen; Bing Wang (Journal of Hazardous Materials, 2024)

A comparative evaluation of the structure, functionality and volatile profiles of Trichosanthes kirilowii seed protein isolates based on different extraction methods - Dong Peng; Zhilin He; Xiangmin Pan; Rui Zheng; Hanxiao Bao; Jingru Liao; Ling Dong; Weiwen Li; Jianping Chen; Pan Li; Bing Du (Food Chemistry, 2024)

Near-infrared laser induced direct ignition of 4,4′,5,5′-tetranitro-1H,1′H-[2,2′-biimidazole]-1,1′-diamine by constructing diverse crystal structures - Ping Ye; Weimiao Wang; Xiaodong Li; Zhiqiang Qiao; Yirui Lu; Bing Huang; Liangfei Bai; Liang Chen; Xiaoqing Tu; Rui Li; Guangcheng Yang; Guoqing Lv (Chemical Engineering Journal, 2024)

Screening androgen receptor agonists of fish species using machine learning and molecular model in NORMAN water-relevant list - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Chang-Er Chen; Guang-Guo Ying; Wen-Jun Shi (Journal of Hazardous Materials, 2024)

Thermo-Hydro-Mechanic-Chemical coupling model for hydrate-bearing sediment within a unified granular thermodynamic theory - Rui Zhou; Bing Bai; Guoqing Cai; Xingxin Chen (Computers and Geotechnics, 2024)

Failure mechanism of rock masses with complex geological conditions in a large underground cavern: A case study - Jin-Shuai Zhao; Shu-Qian Duan; Bing-Rui Chen; Lei Li; Ben-Guo He; Peng-Xiang Li; Guo-Feng Liu (Soil Dynamics and Earthquake Engineering, 2024)

Fe-MOFs/CuS nanocomposite-mediated peroxymonosulfate activation for tetracycline degradation: Boosted dual redox cycles - Rui Ma; Zhijie Chen; Weihang Xu; Ran Yu; Yichu Zhang; Fan Chen; Xiaoming Peng; Bing-Jie Ni; Jin Qian (Journal of Cleaner Production, 2024)

Suitable biochar application practices simultaneously alleviate N2O and NH3 emissions from arable soils: A meta-analysis study - Xiayan Zhang; Lipeng Gu; Dongyang Gui; Bing Xu; Rui Li; Xian Chen; Zhipeng Sha; Xuejun Pan (Environmental Research, 2024)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Triptolide induces PANoptosis in macrophages and causes organ injury in mice - Hong-Rui Zhang; Ya-Ping Li; Zi-Jian Shi; Qi-Qi Liang; Si-Yuan Chen; Yi-Ping You; Tao Yuan; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Apoptosis, 2023)

Does digital economy curb carbon intensity? New insights from China - Rui Yang; Bing Chen; Jing Wu (Environmental Science and Pollution Research, 2023)

Sulfur-decorated Fe/C composite synthesized from MIL-88A(Fe) for peroxymonosulfate activation towards tetracycline degradation: Multiple active sites and non-radical pathway dominated mechanism - Jin Qian; Yichu Zhang; Zhijie Chen; Ran Yu; Yin Ye; Rui Ma; Kailong Li; Lingzhen Wang; Dongqi Wang; Bing-Jie Ni (Journal of Environmental Management, 2023)

Collaborative removal of fine catalysts particles and insoluble organics from methanol-to-olefins reaction wastewater using horizontal swirl regeneration micro-channel separation (HSRMS) - Jianqi Chen; Rui Cai; Haitao Huang; Qi Wei; Bing Liu; Aosong Wei; Meng Zhang; Wenjie Lv; Hualin Wang (Process Safety and Environmental Protection, 2023)

Hierarchical Co-Fe layered double hydroxides (LDH)/Ni foam composite as a recyclable peroxymonosulfate activator towards monomethylhydrazine degradation: Enhanced electron transfer and 1O2 dominated non-radical pathway - Jin Qian; Rui Ma; Zhijie Chen; Gen Wang; Yichu Zhang; Yufei Du; Yongjun Chen; Taicheng An; Bing-Jie Ni (Chemical Engineering Journal, 2023)

Revealing the role of calcium alginate-biochar composite for simultaneous removing SO42− and Fe3+ in AMD: Adsorption mechanisms and application effects - Rui Li; Bing Wang; Pan Wu; Jian Zhang; Xueyang Zhang; Miao Chen; Xingxing Cao; Qianwei Feng (Environmental Pollution, 2023)

Efficient emerging contaminants (EM) decomposition via peroxymonosulfate (PMS) activation by Co3O4/carbonized polyaniline (CPANI) composite: Characterization of tetracycline (TC) degradation property and application for the remediation of EM-polluted water body - Jin Qian; Xiaohui Mi; Zhijie Chen; Weihang Xu; Wen Liu; Rui Ma; Yichu Zhang; Yufei Du; Bing-Jie Ni (Journal of Cleaner Production, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

Abundance and characteristics of microplastics in the Wanquan River estuary, Hainan Island - Tuan-Tuan Wang; Wang-Qing Tang; Dong-Hai Wu; Xin-Rui Yu; Guang-Yu Wang; Xing-Wei Cai; Shuai Shao; Sai Wang; Ling Mo; You-Sheng Liu; Guang-Guo Ying; Zhong-Bing Chen (Marine Pollution Bulletin, 2023)

Exploring the potential anti-Alzheimer disease mechanisms of Alpiniae Oxyphyliae Fructus by network pharmacology study and molecular docking - Rong-Rong Zhen; Yan-Jie Qu; Li-Min Zhang; Chao Gu; Min-Rui Ding; Lei Chen; Xiao Peng; Bing Hu; Hong-Mei An (Metabolic Brain Disease, 2023)

Rockburst and microseismic activity in a lagging tunnel as the spacing between twin TBM excavated tunnels changes: A case from the Neelum-Jhelum hydropower project - Peng-Xiang Li; Bing-Rui Chen; Ya-Xun Xiao; Guang-Liang Feng; Yang-Yi Zhou; Jin-Shuai Zhao (Tunnelling and Underground Space Technology, 2023)

Abnormal fatty acid metabolism and ceramide expression may discriminate myocardial infarction from strangulation death: A pilot study - Song-Jun Wang; Bing-Rui Liu; Fu Zhang; Ya-Ping Li; Xiao-Rui Su; Chen-Teng Yang; Bin Cong; Zhi-Hua Zhang (Tissue and Cell, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Novel and sustainable carboxylation of terminal alkynes and CO2 to alkynyl carboxylic acids using triazolium ionic liquid-modified PMO-supported transition metal acetylacetonate as effective cooperative catalysts - Jing-Rui Li; Chen Chen; Xiao-Bing Liu; Yu-Lin Hu (Environmental Science and Pollution Research, 2022)

Homocysteine-Induced Disturbances in DNA Methylation Contribute to Development of Stress-Associated Cognitive Decline in Rats - Shi-Da Wang; Xue Wang; Yun Zhao; Bing-Hua Xue; Xiao-Tian Wang; Yu-Xin Chen; Zi-Qian Zhang; Ying-Rui Tian; Fang Xie; Ling-Jia Qian (Neuroscience Bulletin, 2022)

A novel microRNA regulates cooperation between symbiont and a laterally acquired gene in the regulation of pantothenate biosynthesis within Bemisia tabaci whiteflies - Xiang Sun; Bing‐Qi Liu; Chu‐Qiao Li; Zhan‐Bo Chen; Xiao‐Rui Xu; Jun‐Bo Luan (Molecular Ecology, 2022)
Horizontally transferred genes (HTGs) play a key role in animal symbiosis, and some horizontally transferred genes or proteins are highly expressed in specialized host cells (bacteriocytes). However, it is not clear how HTGs are regulated, but microRNAs (miRNAs) are prime candidates given their previously demonstrated roles in symbiosis and impacts on the expression of host genes. A horizontally acquired PanBC that is highly expressed in whitefly bacteriocytes can cooperate with an obligate symbiont Portiera for pantothenate production, facilitating whitefly performance and Portiera titre. Here, we found that a whitefly miRNA, novel‐m0780‐5p, was up‐regulated and its target panBC was down‐regulated in Portiera ‐eliminated whiteflies. This miRNA was located in the cytoplasmic region of whitefly bacteriocytes. Injection of novel‐m0780‐5p agomir reduced the expression of PanBC in whitefly bacteriocytes, while injection of novel‐m0780‐5p antagomir enhanced PanBC expression. Agomir injection also reduced the pantothenate level, Portiera titre and whitefly performance. Supplementation with pantothenate restored Portiera titre and the fitness of agomir‐injected whiteflies. Thus, we demonstrate that a whitefly miRNA regulates panBC ‐mediated host–symbiont collaboration required for pantothenate synthesis, benefiting the whitefly– Portiera symbiosis. Both panBC and novel‐m0780‐5p are present in the genomes of six Bemisia tabaci species. The expression of a novel miRNA in multiple B . tabaci species suggests that the miRNA evolved after panBC acquisition, and allowed this gene to be more tightly regulated. Our discovery provides the first account of a HTG being regulated by a miRNA from the host genome, and suggests key roles for interactions between miRNAs and HTGs in the functioning of symbiosis.

Experimental study on the mechanical properties and energy evolution of hard rock during water immersion - Fan-Bo Wei; Bing-Rui Chen; Rui Wang; Guo-Liang Li; Tao Li; Xu Wang; Xin-Hao Zhu (Arabian Journal of Geosciences, 2022)

Petrogenesis and tectonic setting of the early-middle triassic subduction-related granite in the eastern segment of East Kunlun: evidences from petrology, geochemistry, and zircon U-Pb-Hf isotopes - Zuo-Chen Li; Xian-Zhi Pei; Paul D. Bons; Rui-Bao Li; Lei Pei; Guo-Chao Chen; You-Xin Chen; Cheng-Jun Liu; Meng Wang; Shao-Wei Zhao; Xiao-Bing Li; Feng Gao (International Geology Review, 2022)

Microseismic Monitoring of Rock Mass Fracture Response to Blasting Excavation of Large Underground Caverns Under High Geostress - Jin-Shuai Zhao; Bing-Rui Chen; Quan Jiang; Jian-Fei Lu; Xian-Jie Hao; Shu-Feng Pei; Fei Wang (Rock Mechanics and Rock Engineering, 2022)

Transcriptome Analysis Reveals Molecular Mechanisms Underlying Methyl Jasmonate-mediated Biosynthesis of Protopanaxadiol-type Saponins in Panax notoginseng Leaves - Ying Li; Yuan Lin; Bing Jia; Geng Chen; Huineng Shi; Rui Xu; Xuejiao Li; Junrong Tang; Qingyan Tang; Guanghui Zhang; Jianli Yang; Wei Fan; et al. (Journal of Plant Biology, 2022)

Correction to: Temporal and spatial evolution patterns of drought in China over the past 500 years - Cuixia Wei; Bing Guo; Wenqian Zang; Fei Yang; Yuefeng Lu; Dafu Zhang; Hongwei Wu; Xiaoyan Zhen; Haorun Xue; Chao Meng; Shuting Chen; Xiao Yang; et al. (Arabian Journal of Geosciences, 2021)

Microseismic source location method based on a velocity model database and statistical analysis - Bing-Rui Chen; Tao Li; Xin-Hao Zhu; Fan-Bo Wei; Xu Wang; Ming-Xing Xie (Arabian Journal of Geosciences, 2021)

Research progress in bioremediation of petroleum pollution - Yong Yang; Zhan-Wei Zhang; Rui-Xia Liu; Hai-Yan Ju; Xue-Ke Bian; Wan-Ze Zhang; Chuan-Bo Zhang; Ting Yang; Bing Guo; Chen-Lei Xiao; He Bai; Wen-Yu Lu (Environmental Science and Pollution Research, 2021)

A Deep Learning Method for Bias Correction of ECMWF 24–240 h Forecasts - Lei Han; Mingxuan Chen; Kangkai Chen; Haonan Chen; Yanbiao Zhang; Bing Lu; Linye Song; Rui Qin (Advances in Atmospheric Sciences, 2021)
Correcting the forecast bias of numerical weather prediction models is important for severe weather warnings. The refined grid forecast requires direct correction on gridded forecast products, as opposed to correcting forecast data only at individual weather stations. In this study, a deep learning method called CU-net is proposed to correct the gridded forecasts of four weather variables from the European Centre for Medium-Range Weather Forecast Integrated Forecasting System global model (ECMWF-IFS): 2-m temperature, 2-m relative humidity, 10-m wind speed, and 10-m wind direction, with a forecast lead time of 24 h to 240 h in North China. First, the forecast correction problem is transformed into an image-to-image translation problem in deep learning under the CU-net architecture, which is based on convolutional neural networks. Second, the ECMWF-IFS forecasts and ECMWF reanalysis data (ERA5) from 2005 to 2018 are used as training, validation, and testing datasets. The predictors and labels (ground truth) of the model are created using the ECMWF-IFS and ERA5, respectively. Finally, the correction performance of CU-net is compared with a conventional method, anomaly numerical correction with observations (ANO). Results show that forecasts from CU-net have lower root mean square error, bias, mean absolute error, and higher correlation coefficient than those from ANO for all forecast lead times from 24 h to 240 h. CU-net improves upon the ECMWF-IFS forecast for all four weather variables in terms of the above evaluation metrics, whereas ANO improves upon ECMWF-IFS performance only for 2-m temperature and relative humidity. For the correction of the 10-m wind direction forecast, which is often difficult to achieve, CU-net also improves the correction performance.

Synthesis and biological evaluations of a series of calycanthaceous analogues as antifungal agents - Shaojun Zheng; Rui Zhu; Bing Tang; Lizhuang Chen; Hongjin Bai; Jiwen Zhang (Natural Product Research, 2021)

Microseismicity-based method for the dynamic estimation of the potential rockburst scale during tunnel excavation - Guo-Feng Liu; Quan Jiang; Guang-Liang Feng; Dong-Fang Chen; Bing-Rui Chen; Zhou-Neng Zhao (Bulletin of Engineering Geology and the Environment, 2021)

Temporal and spatial evolution patterns of drought in China over the past 500 years - Cuixia Wei; Bing Guo; Wenqian Zang; Fei Yang; Yuefeng Lu; Dafu Zhang; Hongwei Wu; Xiaoyan Zhen; Haorun Xue; Chao Meng; Shuting Chen; Xiao Yang; et al. (Arabian Journal of Geosciences, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Limited sampling strategy for the estimation of the area under the concentration-time curve for ganciclovir in Chinese adult renal allograft recipients - Wen-Bin Rui; Hui-Min An; Kun Shao; Xiao-Hui Zhai; Jia-Qian Lu; Shan-Shan Hu; Bing Chen; Pei-Jun Zhou (European Journal of Clinical Pharmacology, 2019)

Effects of DDIT4 in Methamphetamine-Induced Autophagy and Apoptosis in Dopaminergic Neurons - Bing Li; Rui Chen; Ling Chen; Pingming Qiu; Xiuyun Ai; Enping Huang; Weiye Huang; Chuanxiang Chen; Chao Liu; Zhoumeng Lin; Wei-Bing Xie; Huijun Wang (Molecular Neurobiology, 2017)

A Method for Dynamic Risk Assessment and Management of Rockbursts in Drill and Blast Tunnels - Guo-Feng Liu; Xia-Ting Feng; Guang-Liang Feng; Bing-Rui Chen; Dong-Fang Chen; Shu-Qian Duan (Rock Mechanics and Rock Engineering, 2016)

Arbuscular Mycorrhizal Fungus Alleviates Chilling Stress by Boosting Redox Poise and Antioxidant Potential of Tomato Seedlings - Airong Liu; Shuangchen Chen; Mengmeng Wang; Dilin Liu; Rui Chang; Zhonghong Wang; Xiaomin Lin; Bing Bai; Golam Jalal Ahammed (Journal of Plant Growth Regulation, 2016)

ISRM Suggested Method for In Situ Microseismic Monitoring of the Fracturing Process in Rock Masses - Ya-Xun Xiao; Xia-Ting Feng; John A. Hudson; Bing-Rui Chen; Guang-Liang Feng; Jian-Po Liu (Rock Mechanics and Rock Engineering, 2016)

A Microseismic Method for Dynamic Warning of Rockburst Development Processes in Tunnels - Guang-Liang Feng; Xia-Ting Feng; Bing-rui Chen; Ya-Xun Xiao; Yang Yu (Rock Mechanics and Rock Engineering, 2015)

Umezawaea endophytica sp. nov., isolated from tobacco root samples - Xiao Chu; Bing-Bing Liu; Rui Gao; Zheng-Yu Zhang; Yan-Qing Duan; Salam Nimaichand; Wei Chen; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

Rock Burst Intensity Classification Based on the Radiated Energy with Damage Intensity at Jinping II Hydropower Station, China - Bing-Rui Chen; Xia-Ting Feng; Qing-Peng Li; Ru-Zhou Luo; Shaojun Li (Rock Mechanics and Rock Engineering, 2015)

Microseismic monitoring of columnar jointed basalt fracture activity: a trial at the Baihetan Hydropower Station, China - Bing-Rui Chen; Qing-Peng Li; Xia-Ting Feng; Ya-Xun Xiao; Guang-Liang Feng; Lian-Xing Hu (Journal of Seismology, 2014)

Time-dependent damage constitutive model for the marble in the Jinping II hydropower station in China - Bing-Rui Chen; Xiao-Jun Zhao; Xia-Ting Feng; Hong-Bo Zhao; Shan-Yong Wang (Bulletin of Engineering Geology and the Environment, 2014)

A Three-Dimensional Finite Element Model for Biomechanical Analysis of the Hip - Guang-Xing Chen; Liu Yang; Kai Li; Rui He; Bin Yang; Yan Zhan; Zhi-Jun Wang; Bing-Nin Yu; Zhe Jian (Cell Biochemistry and Biophysics, 2013)

Effect of sulphate nutrition on arsenic translocation and photosynthesis of rice seedlings - Rui Song; Chen-Yun Zhao; Juan Liu; Jing Zhang; Yan-Xiu Du; Jun-Zhou Li; Hong-Zheng Sun; Hong-Bing Zhao; Quan-Zhi Zhao (Acta Physiologiae Plantarum, 2013)

Hemoglobin-Induced Nitric Oxide Synthase Overexpression and Nitric Oxide Production Contribute to Blood–Brain Barrier Disruption in the Rat - Shuo Yang; Yizhao Chen; Xinqing Deng; Weiping Jiang; Bing Li; Zhenghao Fu; Mouxuan Du; Rui Ding (Journal of Molecular Neuroscience, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Pollen morphology and ontogeny of Maianthemum bifolium (L.) F.W. Schmidt in China - Bing-Xiao Chen; Chun-Hai Zhao; Yun-Yun Zhao; Xiao-Rui Liu; Jia-Xi Liu (Plant Systematics and Evolution, 2013)

Protective effect of DNA-mediated immunization with liposome-encapsulated GRA4 against infection of Toxoplasma gondii - Rui Chen; Shao-hong Lu; Qun-bo Tong; Di Lou; Dong-yan Shi; Bing-bing Jia; Guo-ping Huang; Jin-fu Wang (Journal of Zhejiang University-SCIENCE B, 2009)